GAYA HIDUP SUKU BATAK YANG MENDERITA PENYAKIT JANTUNG KORONER (STUDI ETHNOGRAFI DI RSUD DR. PIRNGADI MEDAN TAHUN 2018) - AZRIANA .; MYRNAWATI CRIE HANDINI; ASIMA SIRAIT (LP2MTBM MAKARIOZ, 2019)
The research aimed to find out the lifestyle of Batak tribes who suffer from coronary heart disease at Dr.General Hospital Pirngadi Medan in 2018. The implementation of this research starts from March 2018 to August 2018. This research is a type of qualitative research. The informants from this study were Batak tribe patients suffering from coronary heart disease> 5 years, doctors and king parhata as validity of the data. Data collection techniques in research use observation and in-depth interviews. The results of this study found the lifestyle of the Batak tribe which is a risk factor for coronary heart disease is due to the many parties in the Batak tribe. Lifestyle is a risk factor for coronary heart disease due to fatty food eating habits at parties. This fatty food can be obtained from typical Batak foods, namely saksang, Tanggo-Tanggo and jambar with beef, buffalo and pork compositions. In addition, during the party drinking wine or alcohol, which is often drunk by the average male. How to control coronary heart disease is by way of self discipline by doing a healthy lifestyle. Batak tribal culture must be followed because it is to honor the ancestors and to keep the traditions of the heretics that have been determined by the ancestors. The conclusion of this study that the lifestyle of the Batak tribe which is a risk factor for coronary heart disease is due to the many parties in the Batak tribe. The number of Batak tribal parties which are attended by various forms of food and drink without controlling the food, can cause the risk of coronary heart disease.